PENGARUH PEMBELAJARAN KOOPERATIF TIPE TGT DAN GAYA BELAJAR MODEL VARK TERHADAP HASIL BELAJAR KIMIA SEKOLAH PADA MAHASISWA PROGRAM STUDI PENDIDIKAN KIMIA - Kurniati, Tuti; Kurniawan, Rizmahardian Ashari (Universitas Tanjungpura, 2017)
This research aims to investigate the effects of Teams Games Tournament (TGT) cooperative technique and VARK learning style student for learning School of Chemistry. This research using quasy experiment with 2 independent variables, TGT cooperative technique and VARK learning style, and 1 dependent variable, learning outcome. The subjects are students of Education of Chemistry in Muhammadiyah University. The instruments were test, documentation, and questioner. The hypothesis test is 0,00 so it achieved a significant learning outcome in experimental group class. The result of effect size show 1,415, categorized in the high category and give the significant learning outcome.Keywords: School of Chemistry, Learning Style, Teams Games Tournament (TGT)